Dampak UU Harmonisasi Peraturan Perpajakan Terkait Perlakuan PPN Perusahaan Pertambangan - Alif Nurdin, Dahlan; Septriadi, Danny (Politeknik Ganesha Medan, 2024)
Regulations regarding Value Added Tax (VAT) have undergone changes with the enactment of Law No. 7 of 2021 on Tax Regulation Harmonization. One of the changes in the Tax Regulation Harmonization Law is the change of coal from non-taxable goods to taxable goods. This change will have an impact on the additional reporting obligations and the burden of collecting VAT on coal companies. In terms of input tax credit, companies can choose either to be credited to reduce output tax or to be charged, thus reducing the company's profits. PT XYZ is a private company engaged in the coal mining sector. The data used in this study are primary data in the form of interview results and secondary data in the form of documentation related to the imposition of coal as a taxable good. This study provides an overview that changes in the treatment of coal from non-taxable goods to taxable goods have an impact on the company's financial performance. With the inclusion of coal as taxable goods, companies must adjust their tax management whether to credit input tax or finance their input tax.